Weaning from mechanical ventilation in post- operatory cardiac surgery: a clinical trial - Marcia Ribeiro Braz; Marluci Andrade Conceição Stipp (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The cardiac surgery post-operatory nurses from Hospital Universitário Pedro Ernesto use syncronized Intermittent mandatory ventilation (SIMV) as a weaning method. Extubation occurs, in average, eight hours after surgery, what is considered a long period. The study compares the period of mechanical ventilation between two weaning modalities: T-tube and SIMV. The study refers to a randomized, clinical trial and control group. A mechanical ventilation weaning protocol has been developed utilizing T-tube as a way of comparing the current protocol, which utilizes SIMV. A Student t- test has been perfomed for the comparison of both groups, with the help of 3.0 Instat GraphPad. The values were considered significant at p<0,05. It was approved by The Research Ethics Committee of the Institution. In the previous analysis, on comparing the time between the two techniques, the use of T-tube was the modality when the patients were weaned in a shorter period of time (45 minutes). However, the values have not been considered significant due to the small size of the sample (n=30). It has been noted that the higher the level of sedation in the post-operatory phase, the faster the weaning. This finding has been related with the absence of pain felt at this stage; once the patient without pain cooperates in the weaning process. The pain limits the movement. As a result, coughing, deep breathing and change in position will be restrained. Therefore, the patient will be agitated at awakening, being necessary the restraint of his movements in bed, prolonging sedation and extubation.